Rancang Bangun Aplikasi Perhitungan Investasi Budidaya Pembesaran Ikan Lele Studi Kasus Kelompok Tani Makmur Dan Mina Tani Sebani Kecamatan Tarik Kabupaten Sidoarjo - Dharmawan, Agus; Sunarto, M.J. Dewiyani; Widodo, Arifin Puji (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Sidoarjo regency is one of the central areas of fish production for the province of East Java. In 2014 the Sidoarjo regency produces fish production of 16 911 tonnes of the total demand of 21,190 tons. People therefore have the potential to Rp. 64.3245 billion, - to be used. However, with the opportunities that still makes people hesitant. Based on observations and interviews, people have some problems in understanding the business opportunities the business of enlarging catfish. The problems regarding the planning is there is no information about the capital, the estimated cost, the information behind the capital and feasibility analysis. In addition, the educational background of different society and do not have the financial complex science that makes people not do the planning before doing business. Based on the above issues then made an application investment calculations enlargement catfish farming berbabasis web by comparing various media pool that can perform calculations, measurement and analysis process using the Cost of Production (HPP), and Average Rate of Return (ARR). Based on the results of trials that have been done this application can display information capital planning, cost estimating, value of turnover as well as the comparison with the 3 (three) media pool. From the calculation using the average rate of return that has been done to produce a value which is to cement pond 4.03. For the pool tarp 2.3. And for ground pools 3.95.